COST AND CUSTOMERS DEMAND DURING OUTSOURCING BETWEEN EUROPEAN AND CHINESE COMPANIES - YAO, Shengtai (2006)
Just look at the back of the TV or fridge in your living room, probably you can find sign said Made in China. Today, more and more products have been manufactured in China such as iPod, toy, clothes, PC and so on. Why do companies keep investing in China for outsourcing? Is low labour cost the only main reason?